2011
DOI: 10.1111/j.1476-5381.2010.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Tocotrienol is a novel inhibitor of constitutive and inducible STAT3 signalling pathway in human hepatocellular carcinoma: potential role as an antiproliferative, pro‐apoptotic and chemosensitizing agent

Abstract: BACKGROUND AND PURPOSEActivation of signal transducer and activator of transcription 3 (STAT3) play a critical role in the survival, proliferation, angiogenesis and chemoresistance of tumour cells. Thus, agents that suppress STAT3 phosphorylation have potential as cancer therapies. In the present study, we investigated whether the apoptotic, antiproliferative and chemosensitizing effects of g-tocotrienol are associated with its ability to suppress STAT3 activation in hepatocellular carcinoma (HCC). EXPERIMENTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 95 publications
2
79
0
Order By: Relevance
“…Therefore, it is very important to identify new effective drugs. Among natural compounds from a variety of plants, diosgenin , b-escin (Tan et al 2010), butein ) and c-tocotrienol (Rajendran et al 2011a) were reported to inhibit proliferation and to induce apoptosis of HCC cells concomitantly in order to downregulate various STAT3-regulated gene products, including cyclin D1, Bcl-2, Bcl-xL, survivin, Mcl-1 and VEGF. These four natural molecules inhibited constitutive and inducible activation of STAT3 through the inhibition of c-Src, JAK1 and JAK2 activation.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Therefore, it is very important to identify new effective drugs. Among natural compounds from a variety of plants, diosgenin , b-escin (Tan et al 2010), butein ) and c-tocotrienol (Rajendran et al 2011a) were reported to inhibit proliferation and to induce apoptosis of HCC cells concomitantly in order to downregulate various STAT3-regulated gene products, including cyclin D1, Bcl-2, Bcl-xL, survivin, Mcl-1 and VEGF. These four natural molecules inhibited constitutive and inducible activation of STAT3 through the inhibition of c-Src, JAK1 and JAK2 activation.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Natural agents, peptides, platinum compounds and other small molecules have been used to inhibit STAT3 activity in various tumor models including HCC [258]. Our group has identified number of STAT3 inhibitors including diosgenin, β-escin, γ-tocotrienol, butein, honokiol, and celastrol that can suppress growth and induce apoptosis in diverse HCC cell lines [259][260][261][262][263][264]. In addition, Chen and coworkers recently reported that a novel obatoclax derivative, SC-2001, can induce apoptosis in hepatocellular carcinoma cells through SHP-1-dependent STAT3 inactivation [265].…”
Section: Pharmacological Inhibition Of Stat3 Activation Pathway In Hccmentioning
confidence: 99%
“…The effect of g-tocotrienol on cell proliferation was determined by the MTT uptake method as described previously (20). The cells (5,000 per well) were incubated with g-tocotrienol in triplicate in a 96-well plate and then incubated for indicated time points at 37…”
Section: Cell Proliferation Mtt Assaymentioning
confidence: 99%
“…However, while tocopherols had been intensively studied for their health benefits, many novel benefits of tocotrienols are only beginning to be brought to light by research in the last decade (13,14). For instance, g-tocotrienol has been reported to suppress the proliferation of a wide variety of tumor cells (15), including gastric (16)(17)(18)(19), hepatocellular carcinoma (20), melanoma (21), breast (22), colorectal (23), and prostate (24). In vivo mice studies have shown that g-tocotrienol can suppress the growth of breast tumor (25), prostate (26), lung cancer and melanoma (27) and also inhibit the growth of liver and pancreatic cancer either alone or in combination with chemotherapeutic drugs and radiation (28,29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation